"Influencia de la temperatura y la agitación del medio corrosivo constituido por h2so4-0.5 m y hcl-0.5 m, sobre la velocidad de corrosión del acero astm a192, medido mediante diferentes técnicas electroquímicas” - Lezama Vergara, Gary Cristhian (2014)
ASTM A192 is widely employed for boiler tubing and steam piping in thermal power plants. Scale formation in internal surface of boiler tubes is one of the major problems in most of high-pressure boilers of thermal power stations. Two major problems result from deposit fouling on the interior tube surface: (1) Loss of heat transfer, and (2) Under-deposit corrosion. Therefore, it is necessary to clean, and mineral acids are typically employed for this purpose. The present study addresses the corrosion behavior of ASTM A192 steel in hydrochloric and sulfuric acid solution at different temperature and agitation using different technique electrochemical. The relationship between the rate of corrosion on ASTM A192 steel and the temperature of the acid medium follows the Arrhenius kinetic model. The increase of the temperature and agitation of the acid medium produced on the surface of the ASTM A192 steel a depolarization of the reaction of hydrogen evolution, which contributes to the increase in the rate of corrosion. Also, the corrosion rate in HCl-0.5M is slightly greater than in H2SO4-0.5M, therefore, the acid cleaning process for boiler components made of ASTM A192 steel will be satisfactory, when performed in any of the evaluated media without stirring (method of filling and soaked) and at temperature up to 65 oC